Development of acid-resistant winter rye Kiprez variety - E. I. Utkina; L. I. Kedrova; E. A. Shlyakhtina; E. S. Parfyenova; N. A. Nabatova; M. G. Shamova (Аграрная наука Евро-Северо-Востока)
The current trend of winter rye breeding for the conditions of northern agriculture is development of aluminum and acid-tolerant cultivars. Studies were carried out in the central zone of the Kirov region in 1991-2019. The complex natural provocative background was used (aluminum ion content 25.5-26.7 mg/100 g of soil at a pH of salt extract 3.6-3.8; annual epiphytotic development of pink snow mold Microdochium nivale (Fr.). Winter-resistant and adaptive cv. Kirovskaya 89 served as the initial material. A rigid natural provocative background made it possible to select the best plants (500 pieces) that were transplanted in spring to an isolated area. Subsequent negative selections, field and laboratory assessments made it possible to create the Kiprez population. During the period of 1995-2013 population reproduction was carried out on a provocative background and 5 cycles of negative selection with simultaneous study in competitive varietal testing on two soil backgrounds. The first selection cycle contributed to an increase in the yield of the new population under conditions of edaphic stress over the original cv. Kirovskaya 89 by 12.6%; the second and third by 19.5 and 29.3%, respectively. Further selection did not show a significant effect. Since 2010, the further improvement of the cv. Kiprez has been carried out using individual-family selection and paired crosses. A multi-year competitive test (2014-2019) showed the advantage of the cv. Kiprez over the standard and the initial cultivar. The average yield increase to the Kirovskaya 89 variety under conditions of slightly acidic soils (pH − 5.3-5.7; Al3+ − 5.0-6.5) was 0.50 t / ha (Kirov) and 0.75 t/ha (Falenki); in the conditions of edaphic stress − 1.91 t / ha (Falenki). A combination of aluminum- and acid tolerance of the cultivar with drought resistance was revealed. In 2014, with a moisture deficit (31% of the norm) in the grain filling and ripening phase, cv. Kiprez exceeded significantly the cv. Falenskaya 4 (standard) by 0.82 tons/ha (19.1%) in a acidic background; initial cv. Kirovskaya 89 - by 1.97 tons/ha (62.7%). Cv. Kiprez is recommended for cultivation on low-fertile soils in harsh hydrothermal conditions of northern agriculture.